Stylistic behavior in construction sentence conditions (order style) - Khansa Saad Fajr; Muhannad Marmous Abboud (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study is based on the poetic stanzas of the poets of the Andalusian era, specifically (the poetry of nature) for them. The study came to achieve objectives, perhaps the most important of which are, Monitoring the required structural methods in the texts of nature poetry, Describe the patterns of the imperative construction sentence as the reality of use in those poetic syllables, such as the interrogative sentences, the command, the prohibition...etc. Revealing the figurative rhetorical meanings included in the required constructional methods in the (Andalusian) nature poetry. After we have crossed that path in the field of this research marked ... (Stylistic behavior in the conditions of the construction sentence (the method of demand) To summarize the most important results: This study provided a statistic for each structural style of demand in the nature poetry of the Andalusian poets, this study presented a picture of the required construction sentence, as it was used in nature poetry.